Scollay Square, ca. 1955 - Neiley, Robert (Tufts Archival Research Center, 2005)
Street-level view of Scollay Square. Signage and light fixtures adorn several of the buildings included in the photograph, including 55 Scollay Square, which is visible in the center of the photograph. Street lights, traffic signs and signals line the sidewalks, and automobiles fill Scollay Square. 7 5/8 x 9 1/2, 8 x 9 15/16 overall Photographs